Situation Report: Bulgaria, 25 June 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. National Assembly Session The Sudanese President's Visit to Bulgaria CC Department for Art and Culture Created Again Ivan Abadzhiev in Finland The Artists' Congress Ends Bulgarian Ministers on Visits Abroad